Moderated moderation modelling of subjective social status, pocket money and depressive symptoms of university students in Ghana - Quansah, Frank; Srem-Sai, Medina; Agormedah, Edmond Kwesi; Ankomah, Francis; Hagan, John Elvis; Schack, Thomas (Frontiers in Public Health, 2024)
Introduction Although the relationship between subjective social status and depression in university students has been well-established, this association could be seen as a spurious one. Previous studies have shown that key variables like financial resources and age could play key roles in explaining the variances in social status and mental health outcomes. In this research, we assessed the complex interrelationships between subjective social status, financial resources at their disposal and depressive symptoms among university students within their young and middle adulthood stages. Methods A cross-sectional survey was conducted in a university in Ghana to sample 1134 university students through accidental sampling. The McArthur Scale and WHO-5 Well-being measure were used for the data collection. Results The results revealed that higher levels of subjective social status were associated with lower levels of depression. It was further found that the interaction between students’ pocket money and age played unique roles in the relationship between subjective social status and depression. Conclusion The study findings call on stakeholders in education to explore funding opportunities and to examine ways of empowering parents (financially) to adequately support the students. Health educationists and promoters, including psychologists, school counsellors and parents could compliment these efforts by helping to train and empower students through self-regulation or management skills to help improve their well-being. Continuous efforts are required to improve the financial status and mental health of students.